Perlindungan Hukum Terhadap Pelaku Usaha Jasa Penyewaan Mobil Yang Mengalami Kerugian Akibat Dari Kelalaian Konsumen - Heluth, Muttaqien; Pesulima, Theresia Louize; Sopamena, Ronald Fadly (PATTIMURA Law Study Review, 2024)
ABSTRACT: Rental agreements, general provisions apply regarding the conditions for the validity of the agreement as regulated in Article 1320 of the Civil Code, one of which is the word of agreement to enter into an agreement, meaning that both parties must have freedom of will. Regarding agreements in an agreement, it is certain that the parties implementing it want performance, but not infrequently in an agreement it is inevitable that legal events will occur in the form of non-fulfillment of performance by one of the parties. Default in the implementation of the agreement as mentioned above is an obstacle in the implementation of the rental agreement which generally occurs due to negligence on the part of the lessee. The aim of this research is to examine legal protection for car rental service business actors and the legal remedies that can be taken by car rental service business actors who experience losses as a result of consumer negligence. The method used in this research is normative juridical, namely a legal research method carried out by examining library materials and secondary data including primary and secondary legal sources which are analyzed qualitatively using conceptual and statutory approaches to answer existing problems. The results obtained from this research are legal protection for car rental service business actors for acts of consumer default, namely preventive legal protection which has been regulated in Article 6 of Law Number 8 of 1999 concerning Consumer Protection regarding the right to receive payments in accordance with agreements and rights. to obtain legal protection from consumer actions with bad intentions as well as the right to carry out appropriate self-defense in the legal resolution of consumer disputes and repressive legal protection, namely in the form of compensation as a form of legal responsibility for the tenant's acts of default or negligence in the car rental agreement. The legal action that can be taken by business actors providing car rental services is by means of deliberation (family) regarding payment and time period as well as compensation for losses that must be borne by the car renter. However, if this is not successful, other legal remedies that can be taken are through court and outside court.